X‐ray total scattering investigation of Al0.57Sn0.43O1.71 nanoparticles. (3rd December 2015) - Yavuz, Murat; Knapp, Michael; Indris, Sylvio; Hinterstein, Manuel; Donner, Wolfgang; Ehrenberg, Helmut
Abstract : X‐ray pair distribution function (PDF) analysis of Al0.57 Sn0.43 O1.71, a promising candidate as anode material for Li ion batteries, has been carried out using synchrotron radiation at 60 keV. The average and short‐range ordering of nanocrystalline Al0.57 Sn0.43 O1.71 was investigated both with the traditional Rietveld refinement method and with X‐ray PDF analysis. The instrumental parameters of the high‐resolution powder diffraction beamline P02.1, Petra III, have been characterized. Reverse Monte Carlo (RMC) refinements based on PDF data indicate that Al substitution induces local distortions around the Al/Sn atoms and that oxygen vacancies, induced by the Al substitution, are mostly located on an anion site around the Al atoms. Additionally, RMC refinements hint at a clustering of Al atoms.